(untitled) (Research, Society and Development, 2021)
With the emergence of Chikungunya arboviruses with its outbreaks and changes in its epidemiology in Brazil, the theoretical-methodological framework of Scoping Review was carried out aimed to prepare a systematic summary of global scientific knowledge and understand the practices and prevention programs of Chikungunya with actions information, education, and communication in health developed in countries with risk areas. References were searched in eight databases until October 2018. Of the 376 articles, 177 were duplicates. Applying the exclusion criteria for reading the title and abstract, 145 were excluded, being considered 19 potentially relevant articles. Health information confers its domain in the literature in entomological and epidemiological surveillance, pointing out challenges for the continuing education of health professionals. Actions for vector control and prevention – especially those related to risk communication – have not influenced behavior, driving only punctual changes, that is, attitudes. However, there is a tendency not to consider community and popular knowledge and practices, as well as the active participation and protagonist of the population.